207k views
0 votes
Find f. f ″(x) = x^−2, x > 0, f(1) = 0, f(6) = 0

1 Answer

5 votes

If you do in fact mean
f(1)=f(6)=0 (as opposed to one of these being the derivative of
f at some point), then integrating twice gives


f''(x) = -\frac1{x^2}


f'(x) = \displaystyle -\int (dx)/(x^2) = \frac1x + C_1


f(x) = \displaystyle \int \left(\frac1x + C_1\right) \, dx = \ln|x| + C_1x + C_2

From the initial conditions, we find


f(1) = \ln|1| + C_1 + C_2 = 0 \implies C_1 + C_2 = 0


f(6) = \ln|6| + 6C_1 + C_2 = 0 \implies 6C_1 + C_2 = -\ln(6)

Eliminating
C_2, we get


(C_1 + C_2) - (6C_1 + C_2) = 0 - (-\ln(6))


-5C_1 = \ln(6)


C_1 = -\frac{\ln(6)}5 = -\ln\left(\sqrt[5]{6}\right) \implies C_2 = \ln\left(\sqrt[5]{6}\right)

Then


\boxed{f(x) = \ln|x| - \ln\left(\sqrt[5]{6}\right)\,x + \ln\left(\sqrt[5]{6}\right)}

User David Vereb
by
5.2k points